Genetic transformation of banana and plantain (Musa spp.) via particle bombardment - Sági, L.; Panis, Bartholomeus; Remy, S.; Schoofs, H.; Smet, K. de; Swennen, Rony L.; Cammue, B.P.A. (1995)
We have developed a simple protocol to allow the production of transgenic banana plants. Foreign genes were delivered into embryogenic suspension cells using accelerated particles coated with DNA. Bombardment parameters were optimized for a modified particle gun resulting in high levels of transient expression of the β-glucuronidase gene in both banana and plantain cells. Bombarded banana cells were selected with hygromycin and regenerated into plants. Molecular and histochemical characterization of transformants revealed the stable integration of the transferred genes into the banana genome.